Model Kepemimpinan Ideal Pada Fak Tarbiyah dan Keguruan : Studi Kasus di IAIN Sultan Amai Gorontalo - Herson Anwar; Lian G. Otaya (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This article is aimed to analyse the servant leadership model in achieving and reaching the vision and mission of the Faculty of Tarbiyah and Teaching Training because this model becomes an important issue applied by the education leaders. The research methodology used in this research is quantitative research with mixed method approach by Creswell. The primary data are collected though by questionnaire and secondary data by interview and documentation. The sample consists of 36 respondents by using purposive sampling technique. The result shows that from ten characteristics of servant leadership model, there are seven models implemented well. Those seven models are listening, achieving other people and emphatic, awareness, building persuasive power, service-ability, commitment, and building community. There are three models need to be improved, those are predicting ability, conceptualization, and healing ability. This leadership model is not an instant solution to solve the problem faced by the leader, but it is a long-term way, which the result comprehensively gives the change of vision and mission achievement.